2019
DOI: 10.1177/1687814019891555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of driver stress level with survey, galvanic skin response sensor data, and force-sensing resistor data

Abstract: Thousands of lives are lost in traffic accidents every year, and most traffic accidents are caused by driver errors. Causes and impairments such as fatigue, inattentiveness, alcohol usage, stress, and drugs are the main factors of these accidents. When a driver is subject to changing and complicated driving tasks in traffic, he or she should be able to assure driving authority to prevent potential hazards and accidents. In this context, the purpose of this study is to determine the stress level of the driver w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
0
4
1
1
Order By: Relevance
“…The authors suggest that drivers are to some extent aware of the factors which endanger their well-beingthe subsequent stress response being a reaction to a threat posed by others' behaviour. In contrast to Dogan et al (2019), there were no differences in stressors found between sex or age groups. Seemingly one will be stressed by socially interactive events in the driving environment regardless whether they be male, female, younger or older.…”
Section: Driving Stresscontrasting
confidence: 75%
See 2 more Smart Citations
“…The authors suggest that drivers are to some extent aware of the factors which endanger their well-beingthe subsequent stress response being a reaction to a threat posed by others' behaviour. In contrast to Dogan et al (2019), there were no differences in stressors found between sex or age groups. Seemingly one will be stressed by socially interactive events in the driving environment regardless whether they be male, female, younger or older.…”
Section: Driving Stresscontrasting
confidence: 75%
“…Potentially, the reaction of the driver in relation to perceived discourtesy works in the same way whether the reaction elicited is stress or anger. Experience and frequency of driving also play a part in the stress response of drivers, inexperienced drivers/those who drive infrequently displaying higher subjective stress responses, as well as higher physiological stress responses (as measured by galvanic skin response; Dogan et al, 2019). Moving from purely driving stress to extraneous stress and driving outcomes, Rowden et al (2011) demonstrated that life stress and work stress are also of import in a driving contextpoorer mental health and greater levels of daily hassles were implicated in driving errors, lapses and violations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, it was found that there is a relationship between the driver's stress level and the galvanic skin response of the driver [28]. In this study, different takeover times are applied to the same driver in the same traffic scenarios.…”
Section: Experimental Designmentioning
confidence: 95%
“…Berbeda hal nya dengan Amidei dan rekan yang telah melakukan pendekatan pada parameter konduktivitas kulit terhadap kondisi kantuk seorang pengemudi kendaraan [13], di mana jika kondisi konduktivitas kulit menunjukkan kondisi kantuk maka sistem akan memberikan peringatan kepada pengemudi agar terhindar dari kecelakaan. Begitu juga yang dilakukan oleh Dogan dan rekan yang melakukan hal yang sama Amidei dan rekan yaitu melakukan tingkat stress para pengemudi menggunakan parameter GSR [14]. Bahkan GSR juga telah digunakan untuk mendeteksi tingkat stress pelajar selama kondisi bencana COVID- 19 [15] dan kondisi lapar seorang pasien tertentu yang sulit mengungkapkan kondisi tersebut secara lisan [16].…”
Section: Pendahuluanunclassified